24-hour blood pressure variability and treatment effect of intravenous alteplase in acute ischaemic stroke. (June 2021) - Barow, Ewgenia; Boutitie, Florent; Cheng, Bastian; Cho, Tae-Hee; Ebinger, Martin; Endres, Matthias; Fiebach, Jochen B; Fiehler, Jens; Nickel, Alina; Puig, Josep; Roy, Pascal; Lemmens, Robin; et al.
Introduction: To assess the association between 24 h blood pressure variability (BPV) on functional outcome and treatment effect of intravenous alteplase in acute ischaemic stroke. Patients and methods: In all patients with acute ischaemic stroke of unknown onset randomised in the WAKE-UP (Efficacy and Safety of magnetic resonance imaging [MRI]-based Thrombolysis in Wake-Up Stroke) trial, blood pressure (BP) was measured before randomisation and after initiation of treatment at regular intervals up to 24 hours. Individual BPV was measured by coefficient of variation (CV) of all BP values. Primary outcome measure was favourable outcome defined by a modified Rankin Scale (mRS) score 0 or 1 at 90 days after stroke. Results: BP measurements were available for 498 of 503 patients randomised (177 women [35.5%], mean age [SD] of 65.2 [11.5] years). Systolic BPV was not associated with the treatment effect of thrombolysis (test for interaction, p = 0.46). The adjusted odds ratio (aOR) for favourable outcome with alteplase, adjusted for age, stroke severity and baseline BP on admission, did not show an association across the quintiles of increasing systolic BPV with an aOR 1.89 (95% confidence interval [CI], 0.76–4.70) in the lowest quintile to aOR 1.05 (95% CI, 0.43–2.56) in the highest quintile. Higher mean systolic BP was associated with a smaller treatment effect of thrombolysis with a significant interaction (p = 0.033). The aOR for favourable outcome with alteplase decreased with quintiles of increasing mean systolic BP from aOR 3.16 (95% CI, 1.26–7.93) in the lowest quintile to aOR 0.84 (95% CI, 0.34–2.10) in in the highest quintile. Conclusions: There was a significant interaction between mean systolic BP and treatment effect of thrombolysis with higher mean systolic BP being associated with poorer outcome. BPV was not associated with outcome after thrombolysis. ClinicalTrials.gov identifier NCT01525290.